Menakar Efisiensi Digital: Studi LCA atas Perubahan Sistem Layanan Administrasi Kependudukan. Studi Kasus: Layanan Pindah Keluar oleh DISPENDUKCAPIL Surabaya - Dimyati, Aufar Fikri; Baihaqy, Ahmed Raecky (CV. Green Publisher Indonesia, 2025)
Digital transformation in public services has become a key strategy to improve efficiency, accessibility, and environmental sustainability. The Government of Indonesia has designated the acceleration of public service digitalization as a national priority to realize inclusive, transparent, and environmentally friendly services exemplified by the City of Surabaya, which has implemented massive digitalization efforts since 2019. This study evaluates the environmental impact of digitalizing the “Pindah Keluar” (Out-Migration) administrative service, one of the services provided by the Department of Population and Civil Registration (DISPENDUKCAPIL) in Surabaya, using a Life Cycle Assessment (LCA) approach. The study compares four service system phases: the manual system (SIAK), LAMPID, KLAMPID, KLAMPID during the COVID period, and the fully digital service (KLAMPID Online). The LCA results show that digitalization significantly reduces paper consumption and transportation-related emissions, with the total environmental impact score decreasing from 87.83 mPt in the manual system to 32.67 mPt in the fully digital system. However, digitalization also leads to increased electricity consumption and reliance on digital infrastructure, indicating a shift in environmental burden from the community (in the form of physical activities such as paper use and transportation) to the service provider institution (in the form of energy consumption by digital infrastructure). These findings highlight that achieving sustainable digitalization, from an environmental burden perspective, requires internal system efficiency and the adoption of environmentally friendly energy sources to minimize the total ecological footprint generated by public service providers.